Innovation as a neoliberal 'silver bullet': critical reflections on the EU's Erasmus + Key Action 2. Issue 1 (2nd January 2022) - Ord, Jon
ABSTRACT: This paper critically evaluates the concept of innovation, in the context of the funding of youth work within Erasmus+ Key Acton 2, but the findings are applicable to other settings which emphasise innovation. The paper argues that, first, innovation is problematic because it lacks a definition. Second, innovation is founded on a neoliberal business model, where solutions are identified and mainstreamed, and the consumer is the ultimate arbiter. Third, the importance of innovation as both context dependent and contested is not appreciated. One result of these problems is that established professional knowledge is undermined, and an emphasis on innovation also has the potential to run counter to the existing established educational practices of youth work. It is argued that innovation is becoming a euphemism for quality, and therefore innovation is taking on the guise of a 'silver bullet' for wider EU policy problems.